Thermal comfort monitoring in aviaries by a real-time data acquisition system - Tiago F. B. Camargo; Robson L. Silva; Márcio Higa; Mônica R. Coutinho; Júlio C. D. de Oliveira; Wagner A. dos S. Conceição (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Thermal comfort inside broiler husbandry facilities is essential in obtaining good results in the production activity. Assessment of adequate thermodynamic conditions requires measurement and control, usually implying costs and specialized maintenance. The objective of this research was to monitor the temperature, relative humidity and air speed distributions by a developed low-cost, open-source and easy-to-use measurement system, using Arduino (hardware) and Scilab (software) for real-time data acquisition. Sensors were installed in a real facility (Cianorte, PR), with measurements for internal ambient (20 sensors for temperature/relative humidity, and two sensors for differential pressure, respectively 0.5 and 1.5 m high) and external ambient (pressure and wind speed, 1.5 m high). Data acquisition system has enabled communication with sensors which are easily read by the computer and stored in a data file. The developed data acquisition system proved to be efficient when applied in a commercial broiler husbandry facility, enabling real-time monitoring for thermal comfort parameters.